Elementi di Meteorologia per la Progettazione Green - Fortelli, Alberto (TRIA Urban Studies, 2021)
The volume has been set up in a friendly manner, and tries to propose Meteorology through images, focusing its attention on the description of the clouds, ethereal presences that almost always provide us precise information about the incoming weather. There are ten kinds of clouds, numerous species and even more numerous varieties, and each of them forms in the sky not by chance but as a consequence of a very precise physical and thermodynamic mechanism that is there developing in the atmosphere. Clouds can be considered the leading actresses of this volume and for each of them the author tried to identify the link between these mechanisms of formation and the probable future evolution of weather conditions. In the book, the most recurring type of cloud is the Cumulonimbus, also called "the storm cloud", since it generates the most intense and devastating meteorological phenomena, such as storms, tornadoes, hailstorms, etc. After having extensively dealt with the phenomena associated with Cumulonimbus, the final part of the volume provides some useful insights to understand the response dynamics of the territory under the stresses induced by extreme rainfall events and, lastly, to identify planning territorial strategies able to reduce the impact on the ground. From this point of view, Green Infrastructures have a considerable potential, in particular if they are considered a key element in an overall plan of adaptation to the complex evolutive dynamics of climate change.